Assessing Attitudes Towards Collaboration of Students in Self-directed Online Groups in Higher Education - García, Consuelo; Privado, Jesús (Communications in Computer and Information Science, 2020)
This research focused on knowing the attitudes that students have about collaboration when they work in self-directed groups in a virtual learning environment. A survey was fulfilled by 75 students of a master’s degree on Education evaluating collaboration within their groups. An EFA was applied to the results and a 5-factor structure was obtained. These factors explain 60.30% of the variance of the questionnaire. The first one, Communication merges conversation, interaction and debate. Secondly, another factor named Trust is highlighted, a belief on the success and well-functioning of the team. The third factor, Cooperation attends to the attitude of sharing and being open to all members. A fourth factor, Cohesion, points to ideas as clearness, efficiency, consensus, roles and goals established. And finally, Coordination factor refers to attitudes to work distribution and acceptance of changes. This structure is aligned with previous literature on groups’ dynamics that point to interaction, sharing, clarity and acceptance without conflicts as main elements of successful collaboration.
Ponencia de la conferencia "1st International Workshop on Higher Education Learning Methodologies and Technologies Online, HELMeTO 2019; Novedrate; Italy; 6 June 2019 through 7 June 2019"
Keywords: assessment; attitudes; collaboration; higher education; Scopus(2)